Impact of In Utero Folate Exposure on DNA Methylation and Its Potential Relevance for Later‐Life Health—Evidence from Mouse Models Translated to Human Cohorts. Issue 3 (13th December 2021) - Kok, Dieuwertje E.; Richmond, Rebecca C.; Adriaens, Michiel; Evelo, Chris T.; Ford, Dianne; Mathers, John C.; Robinson, Natassia; McKay, Jill A.
Abstract : Scope: Persistent DNA methylation changes may mediate effects of early‐life exposures on later‐life health. Human lifespan is challenging for prospective studies, therefore data from longitudinal studies are limited. Projecting data from mouse models of early‐life exposure to human studies offers a tool to address this challenge. Methods and Results: C57BL/6J mice were fed low/normal folate diets before and during pregnancy and lactation. Genome‐wide promoter methylation was measured in male offspring livers at 17.5 days gestation and 28 weeks. Eight promoters were concurrently hypermethylated by folate depletion in fetuses and adults (>1.10 fold‐change; p < 0.05). Processes/pathways potentially influenced by global changes, and function of these eight genes, suggest neurocognitive effects. Human observational and randomized controlled trial data were interrogated for translation. Methylation at birth was inversely associated with maternal plasma folate in six genes (−1.15% to −0.16% per nmol L −1 ; p < 0.05), while maternal folic acid supplementation was associated with differential methylation of four genes in adulthood. Three CpGs were persistently hypermethylated with lower maternal folate ( p = 0.04). Conclusion: Some persistent folate‐induced methylation changes in mice are mirrored in humans. This demonstrates utility of mouse data in identifying human loci for interrogation as biomarkers of later‐life health. Abstract : Methylation refers to DNA markers responsible for gene‐activation. It is investigated if methylation changed in response to maternal folate intake during pregnancy. Eight genes have increased (hyper)methylation in fetal and adult mouse liver in response to maternal folate depletion. In humans, two of these genes are consistently hypermethylated with lower folate during pregnancy, the function of which suggests implications for cognition.